Power System Mode optimization by piecewise-linear approximation of energy characteristics of Power Plants - Gayibov Tulkin; Latipov Sherxon; Uzakov Bakhadir (E3S Web of Conferences, 2019)
The issues of improving of methods and algorithms for power system short-term mode optimal planning are considered. The main disadvantages and calculation difficulties typical for traditional algorithms are described. An effective algorithm for power system mode optimization based on a piecewise- linear approximation of nonlinear dependencies is proposed. Application of the proposed algorithm can effectively increase the accuracy and overcome many calculation difficulties associated with discontinuity of energy characteristics of power plants and various constraints in the form of equality and inequality.